Anti‐spike S1 receptor‐binding domain antibodies against SARS‐CoV‐2 persist several months after infection regardless of disease severity. Issue 5 (23rd February 2021) - Bavaro, Davide F.; Laghetti, Paola; Milano, Eugenio; Brindicci, Gaetano; Volpe, Anna; Lagioia, Antonella; Saracino, Annalisa; Monno, Laura
Abstract: Data regarding the immunological memory and long‐time kinetics of immunoglobulin (IgG) against viral nucleoprotein (NP) and spike protein S1 receptor‐binding domain (S1RBD) of Severe Acute Respiratory Syndrome‐associated Coronavirus 2 (SARS‐CoV‐2) are lacking. All consecutive COVID‐19 patients admitted to our Clinic between March 1, 2020, and May 1, 2020, who were tested at hospital admission for anti‐S1RBD and anti‐NP IgG were enrolled. Serum samples were tested for anti‐SARS‐CoV‐2 antibodies with the use of two commercially available enzyme‐linked immunosorbent assays. Results are expressed as optical density measurements at 450 nm (OD450 ). Overall, 111 patients were included; the median (q1–q3) age was 57 (49–73) years, 59 (53%) males. According to disease severity, 31 (28%), 47 (42%), and 33 (30%) patients were considered affected by mild/moderate, severe, and critical SARS‐CoV‐2 infection, respectively. During hospitalization, patients with the critical disease showed a higher peak value of both anti‐NP (median OD450 : 3.66 vs. 3.06 vs. 3.00 respectively, p = .043) and anti‐S1RBD IgG (median OD450 : 2.33 vs. 1.6 vs. 0.91, respectively, p < .001). By testing 48 subjects 6 months or above from discharge, a significant decrease of anti‐NP IgG was observed ( r : −0.5838; p < .0001), whereas anti‐S1RBD IgG showed only a modest reduction ( r : −0.1507; p = .0647). Accordingly, 10 (21%) and 2 (4%) patients had a negative serological status for anti‐NP and anti‐S1RBD IgG, respectively; no association with clinical severity was found. IgGs against SARS‐CoV‐2 persisted several months after discharge, regardless of disease severity, suggesting that vaccination could be a valid strategy to fight the pandemic. Highlights: ‐Antibodies against SARS‐CoV‐2 persisted several months after the disease. ‐ Infection severity apparently did not affect IgG seroconversion. ‐ SARS‐CoV‐2 vaccination could be a valid strategy to fight the pandemic.